STRATEGI IMPLEMENTASI PENDIDIKAN ISLAM MODERAT DALAM MEMBENTUK KARAKTER PESERTA DIDIK DI LEMBAGA PENDIDIKAN PESANTREN - Khoirur Rozikin; Ali Ahmad Yenuri (Makkah: Journal Of Islamic Studies, 2026)
Moderate Islamic education is an educational approach that emphasizes the values ​​of balance, tolerance, justice, and an open attitude towards differences in social life. This article discusses the concept of moderate Islamic education, the factors underlying its urgency in Indonesia, its implementation strategies in the world of education, and the challenges and opportunities in its implementation. Indonesia, as a country with a pluralistic society, requires an Islamic education model that can instill the values ​​of unity, love of peace, and respect for diversity. Through a literature review, this article shows that moderate Islamic education plays a crucial role in preventing the development of intolerant and radical attitudes among students. The implementation of moderate Islamic education can be done through the integration of the values ​​of moderation in the curriculum, teacher role models, the creation of an inclusive school culture, and the wise use of learning media. The results of this study confirm that moderate Islamic education is not only conceptually relevant but also strategic in shaping the character of students who are noble, tolerant, and responsible in national and state life.